Application of Tactical Combat Casualty Care in the Management of a Proximal Left Leg Gunshot Wound: From Battlefield to Surgical Amputation – A Case Report - Indra Pehulisa Sitepu; Hafidz Addatuang Ambong (Perkumpulan Kedokteran Militer, 2026)
Gunshot wounds to the lower extremities can cause life-threatening haemorrhage and vascular injury, requiring rapid intervention according to Tactical Combat Casualty Care (TCCC) principles. This case describes a 24-year-old soldier with a proximal left cruris gunshot wound managed initially under fire with a tourniquet, hemostatic agents, analgesia, and tranexamic acid. After delayed evacuation due to battlefield conditions, further stabilization and surgical management revealed open fractures and popliteal artery injury. Despite vascular repair, prolonged ischemia exceeding the golden period resulted in irreversible tissue damage, necessitating amputation. This case highlights that while TCCC effectively improves survival, timely evacuation and early definitive vascular treatment are critical for limb salvage in combat settings.